Holistic approach to the patient in order to optimize treatment of spinal canal tumours - Szweda, Agnieszka; Chantsoulis, Marzena; Świątkowska-Wróblewska, Katarzyna; Sakowski, Jarosław (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Neoplastic lesions of the spinal column can be located either in osseous elements or spinal canal. Apart from the oncologic aspects, spinal canal stenosis, spine instability due to bone destruction, neurologic deficit and severe pain are also indications for surgical treatment. Optimal - holistic process consisting of diagnostic, neurosurgical, nursing and physiotherapeutic management, based on our own experience was discussed. Authors present two patients suffering from tumours located in the spinal canal, qualified for urgent surgical treatment. Optimal - holistic therapeutic process consisting of nerosurgical, nursing and physiotherapeutic management is discussed. Early diagnosis and optimal surgical treatment together with nursing care and intensive perioperative physiotherapy all influence patient’s funcional status and are directly related to the quality of life among people with spinal canal tumours Nursing Topics 2010; 18 (4): 518-522